2019
DOI: 10.1515/jbcpp-2019-0322
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacist contributions in the treatment of diabetes mellitus in Southeast Asia: a narrative review

Abstract: BackgroundThe growing burden of diabetes mellitus (DM) in Southeast Asia puts pharmacists in the ideal position to provide management of DM. This narrative review aims to describe the evidence of pharmacist contribution in improving DM in Southeast Asia.ContentA literature search was conducted to identify relevant research articles published from 2010 to 2018 in four databases (Scopus, Pubmed, MEDLINE, and Springerlink) describing pharmacist roles and activities intended to improve management of DM in Southeas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 30 publications
0
5
0
2
Order By: Relevance
“…A systematic review of pharmacies in South Asia showed that training is needed in the process of identifying pharmaceutical care problems because pharmacists are lacking experience in identifying and tackling care issues. 15 Therefore, relevant government departments should combine the current situation to refine licensed pharmacists and regulations, and coordinate resources to provide a suitable environment. Given respondents’ major, more and more students majoring in pharmacy and traditional medicine contribute to a specialized service team from a forward-looking perspective.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A systematic review of pharmacies in South Asia showed that training is needed in the process of identifying pharmaceutical care problems because pharmacists are lacking experience in identifying and tackling care issues. 15 Therefore, relevant government departments should combine the current situation to refine licensed pharmacists and regulations, and coordinate resources to provide a suitable environment. Given respondents’ major, more and more students majoring in pharmacy and traditional medicine contribute to a specialized service team from a forward-looking perspective.…”
Section: Discussionmentioning
confidence: 99%
“…12 Pharmacists can play the following roles in the comprehensive management of diabetic patients, including improving patient medication compliance, ensuring the rationality of patients' home medication, providing medication education for patients, and participating in medication monitoring for diabetic patients. [13][14][15] Study results from primary literature have shown that the involvement of pharmacists in direct patient care yields additional average HbA1c reductions of 0.88%-1.8%, average systolic blood pressure reductions of 5.7-7.8 mmHg, and average low-density lipoprotein (LDL) reductions of 6.3 mg/dL-18.7 mg/dl, compared with standard care. 16,17 Also, the continuous intervention of the pharmacist is a cost-effective administration method, which improved the quality of life without any increase in spending.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical pharmacists provide several clinical pharmacy services to promote the rational use of medications in diabetic patients, inducing a thorough evaluation of the patient status, providing suggestions on drug treatment to physicians, delivering relevant education to patients. 9,10 Compared to the usual care regime, pharmacist interventions have resulted in favorable improvements in the blood glucose indices including hemoglobin A1c (HbA1c), and fasting blood glucose (FBG), as well as other cardiovascular risk factors involving blood pressure, body mass index (BMI), total cholesterol, low-density lipoprotein, high-density lipoprotein, and triglycerides. 11 However, evidence supporting the effects of clinical pharmacist interventions on the blood glucose fluctuations are limited.…”
Section: Introductionmentioning
confidence: 99%
“…5 A recent systematic review of DMTAC studies from Southeast Asia conducted by Dwiputri et al, concluded that pharmacists can contribute to improve diabetes management in a variety of settings. 6 Of the 16 articles included in the above review, half (8 studies) came from Malaysia. 6 …”
Section: Introductionmentioning
confidence: 99%